Creative fitness : applying health psychology and exercise science to everyday life - Biller, Henry B. (Auburn House, 2002)
Annotation Biller integrates exercise, nutrition, and health issues within an applied developmental psychological framework. Readers are presented with ways of making fitness an enjoyable and positive force in their daily lives. Biller's primary mission is to encourage a healthy lifestyle that enriches self-awareness and personal growth.